1980
DOI: 10.1071/ch9800965
|View full text |Cite
|
Sign up to set email alerts
|

Free-radical reductions of arenediazonium ions in aqueous solution. IV. Kinetics of reactions of para-substituted diazonium ions with benzyl alcohol, isopropyl alcohol and methanol

Abstract: Electron-withdrawing substituents are shown to increase the chain length of free-radical hydrodediazoniation reactions, but the actual reaction step causing the substituent effect depends on the relative rates of propagation and termination reactions. With benzyl alcohol as reducing agent the rate of the slow propagation step is increased, while with isopropyl alcohol the rate of the termination step is decreased. Rate constants for some reactions of radicals with diazonium ions are reported, and the nature of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

1982
1982
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…This observation strengthens our proposal that the aryl radical at C5 possibly arises from a dehydration reaction of the radical anion of TPZ that involves the C5 hydrogen. Such aryl radicals are best described as phenyl-type radicals, which are known to react with purine and pyrimidine bases, cleave DNA nonspecifically, and be inhibited by hydrogen donors such as ethanol and thiol compounds. , In addition, phenyl radicals in vitro are known to abstract an H-atom from added formate ions to form the reducing carbon dioxide radical anion, , which can then reduce electron-affinic compounds. Such a series of reactions may explain the observed removal of the BTO compounds from solution by chain reactions, with the shortness of the chain arising from bifurcation of the precursor radical into a phenyl radical and another radical species (i.e., in the case of TPZ, the BTZ radical 17 ) that does not abstract H-atoms from formate ions or alcohols.…”
Section: Discussionmentioning
confidence: 99%
“…This observation strengthens our proposal that the aryl radical at C5 possibly arises from a dehydration reaction of the radical anion of TPZ that involves the C5 hydrogen. Such aryl radicals are best described as phenyl-type radicals, which are known to react with purine and pyrimidine bases, cleave DNA nonspecifically, and be inhibited by hydrogen donors such as ethanol and thiol compounds. , In addition, phenyl radicals in vitro are known to abstract an H-atom from added formate ions to form the reducing carbon dioxide radical anion, , which can then reduce electron-affinic compounds. Such a series of reactions may explain the observed removal of the BTO compounds from solution by chain reactions, with the shortness of the chain arising from bifurcation of the precursor radical into a phenyl radical and another radical species (i.e., in the case of TPZ, the BTZ radical 17 ) that does not abstract H-atoms from formate ions or alcohols.…”
Section: Discussionmentioning
confidence: 99%
“…Equation 1has been recently postulated in pulse radiolisis studies of arenediazonium salts. 4 Several sources of alkyl radicals R• were found suitable for this reaction. For example, alkyl iodides (RI; R = methyl, primary, secondary, or tertiary alkyl, or benzyl)…”
mentioning
confidence: 99%
“…The latter is formed by the reduction of the diazonium salt and should involve a radical intermediate. The reduction of diazonium salts by alcoholic solvents (here methanol) by de-diazoniation through a homolytic pathway can happen in neutral, [33][34][35][36][37] basic, [38][39][40][41] or acidic [42][43][44][45][46][47][48] media in the presence or absence of water, and the previous work by DeTar and co-workers [39,40,47] showed that it is favored by the presence of acetate in methanol, resulting in the formation of arene and formaldehyde.…”
Section: The Active Copper Speciesmentioning
confidence: 99%